Regression of dermal mast cell infiltrates in patients with cutaneous mastocytosis - Péč, Martin (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2003)
Background. Fourteen children with urticaria pigmentosa (UP) and two with disseminated cutaneous mastocytosis (DCM) were followed. Methods. Three skin biopsies were performed: the first one before the age of 2 years, the second one after 1-year treatment and the third 6 years after the second. Results. The repeated biopsy after the 1-year treatment resulted in a 20-60% regressionof the mast cell infiltrates, while the third one disclosed a 70-90%reduction of these infiltrates. In UP patients the mast cell infiltrate changed from vessel unit type >55 micro m to 55 micro m. In the two nontreated UP patients the mast cell infiltrate type remained <55 micro m.Conclusion: The authors observed a spontaneous regression of the mast cell infiltrates in mastocytosis patients during adolescence; the treatment can however essentially influence their reduction.
Keywords: Biopsija; Biopsy; Child; dermatologija; Drug Therapy; kožne bolezni; Mast Cells; Otrok; Pathology; Tkivni bazofilci; Urticaria Pigmentosa; Urtikarija pigmentna